A systematic review of the evidence on clitoral reconstruction after female genital mutilation/cutting. Issue 2 (May 2015) - Abdulcadir, Jasmine; Rodriguez, Maria I.; Say, Lale
Abstract Background Clitoral reconstruction is a new surgical technique for women who have undergone female genital mutilation/cutting (FGM/C). Objectives To review evidence on the safety and efficacy of clitoral reconstruction. Search strategy PubMed and Cochrane databases were searched for articles published in any language from database inception until May 2014. Search terms related to FGM/C and clitoral reconstruction were used in various combinations. Selection criteria Studies of any design that reported on safety or clinical outcomes (e.g. appearance, pain, sexual response, or patient satisfaction) associated with clitoral reconstruction after FGM/C were included. Data collection and analysis Evidence was summarized and systematically assessed via a standard data abstraction form. Main results Four of 269 identified articles were included. They were fair to poor in quality. Summary measures could not be computed owing to heterogeneity. The studies reported on immediate surgical complications, clitoral appearance, dyspareunia or chronic pain, and clitoral function postoperatively via non-standardized scales. Conclusions Women who request clitoral reconstruction should be informed about the scarcity of evidence available. Additional research is needed on the safety and efficacy of the procedure to identify both long-term outcomes and which women might benefit.